Communication technology for students in special education and gifted programs - Aitken, Joan E.; Fairley, Joy Pedego; Carlson, Judith K.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book collects ideas about new communication technologies and innovative ways of using them to enhance education for students with exceptionalities, offering case studies based on the experiences and expertise of the teachers, researchers, and other professionals who have used them"--Provided by publisher.
13. Signage as a classroom prompt: an evidence-based practice? / Ian J. Loverro David J. Majsterek and David N. Shorr -- 14. Using social bookmarking to make online resources more accessible / Stein Brunvand -- 15. Reflections on teaching students with special needs in an online master's program / Lora Cohn -- 16. Using tactile prompts to increase social-communicative skills with children with autism / Judah B. Axe -- 17. Personal reflections on the educational potential and future of closed captioning on the Web / Sean Zdenek -- 18. Parental communication about the needs of their children: as expressed in an online support group / Joan E. Aitken -- 19. Are you SMARTer than a SMART Board?: How to effectively use this technology tool to communicate in a classroom with a diverse group of learners / Mandi Sonnenberg -- 20. Reading by listening: access to books in audio format for college students with print disabilities / Marni Gail Jones, Christopher L. Schwilk and David F. Bateman -- 21. Integrating accessible multiplication games into inclusive classrooms / Cindy L. Anderson -- 22. Do you see what i'm saying?: Ultrasound technology as a tool for pronunciation instruction / Bryan Meadows -- 23. What do you do with a digital pen? / Judith K. Carlson -- 24. Communication technologies for instructional use: linear and nonlinear tools contributing to student learning / Seok Kang -- 25. Teaching what we don't know: failing to adequately prepare teachers to use technology for the benefit of students with special needs / Joy E. Harris -- 26. Ten hot assistive tech websites that you won't want to miss / Alex Thompson.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 18, 2011).
Keywords: Gifted children -- Education; Learning disabled -- Means of communication; Assistive communication; Assistive technologies; Augmentative communication; Communication technology; Gifted education; Special education; Alternative education; Distance learning; Educational technology; Special programs; Technology assessment; Response to Intervention (RTI); Electronic books